Evaluate this simple sum!

Algebra Level 4

If k = 0 n ( 1 ) k k 3 + 9 k 2 + 26 k + 24 ( n k ) \sum_{k=0}^{n} \dfrac{(-1)^{k}}{k^{3}+9k^{2}+26k+24} \dbinom{n}{k} can be expressed as 1 α ( n + β ) ( n + γ ) \frac{1}{\alpha(n+\beta)(n+\gamma)} for some positive integers α , β , γ , \alpha , \beta , \gamma , what is α + β + γ ? \alpha+\beta+\gamma?


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Ahaan Rungta
Jun 26, 2014

Nice problem, but note that one might say that the following "solution" I present is also known as cheating . So read at your own risk.

Note that, if this problem is not flawed, the relationship given is true and it holds for all n 0 n \ge 0 . There are three unknowns: α \alpha , β \beta , and γ \gamma , so if we have three independent equations relating α \alpha , β \beta , and γ \gamma , we can solve for them.

For n = 0 n = 0 , the sum is k = 0 0 ( 1 ) k k 3 + 9 k 2 + 26 k + 24 ( 0 k ) = 1 24 = 1 α β γ . \displaystyle\sum_{k=0}^{0} \dfrac {\left( -1 \right)^k}{k^3 + 9k^2 + 26k + 24} \dbinom {0}{k} = \dfrac {1}{24} = \dfrac {1}{\alpha \beta \gamma}.

For n = 1 n = 1 , the sum is k = 0 1 ( 1 ) k k 3 + 9 k 2 + 26 k + 24 ( 1 k ) = 1 24 1 60 = 1 40 = 1 α ( 1 + β ) ( 1 + γ ) . \displaystyle\sum_{k=0}^{1} \dfrac {\left( -1 \right)^k}{k^3 + 9k^2 + 26k + 24} \dbinom {1}{k} = \dfrac {1}{24} - \dfrac {1}{60} = \dfrac {1}{40} = \dfrac {1}{\alpha \left( 1 + \beta \right) \left( 1 + \gamma \right)}.

For n = 2 n = 2 , the sum is k = 0 2 ( 1 ) k k 3 + 9 k 2 + 26 k + 24 ( 2 k ) = 1 24 2 60 + 1 120 = 1 60 = 1 α ( 2 + β ) ( 1 + γ ) . \displaystyle\sum_{k=0}^{2} \dfrac {\left( -1 \right)^k}{k^3 + 9k^2 + 26k + 24} \dbinom {2}{k} = \dfrac {1}{24} - \dfrac {2}{60} + \dfrac {1}{120} = \dfrac {1}{60} = \dfrac {1}{\alpha \left( 2 + \beta \right) \left( 1 + \gamma \right)}.

From these, we get the set of equations: α β γ = 24 , α ( 1 + β ) ( 1 + γ ) = 40 , α ( 2 + β ) ( 2 + γ ) = 60. \begin{aligned} \alpha \beta \gamma &=& 24, \\ \alpha \left( 1 + \beta \right) \left( 1 + \gamma \right) &=& 40, \\ \alpha \left( 2 + \beta \right) \left( 2 + \gamma \right) &=& 60. \end{aligned}

At this point, you realize that there are several integer solutions but α > 1 \alpha > 1 is probably the case, so α = 2 \alpha = 2 and β + γ = 7 \beta + \gamma = 7 , giving the answer α + β + γ = 9 . \alpha + \beta + \gamma = \boxed {9}.

It also turns out that this is correct, using WolframAlpha: k = 0 n ( 1 ) k k 3 + 9 k 2 + 26 k + 24 ( n k ) = 1 2 n 2 + 14 n + 24 . \displaystyle\sum_{k=0}^{n} \dfrac {\left( -1 \right)^k}{k^3 + 9k^2 + 26k + 24} \dbinom {n}{k} = \dfrac {1}{2n^2 + 14n + 24}.

Finally, a note to @Abhishek Singh - it is a good habit to name your problems for descriptively. First of all, the title says nothing about the problem itself. Second, it makes people who cannot solve the problem feel bad, since you are calling it "simple" - it may be simple for you but it's definitely not simple for everybody.

Nice "cheating". I tried factoring the denominator and expressing the expression as partial fractions.It worked out fairly well,but then I couldn't see a way to proceed.I think the sum telescopes quite easily but I can't find a good way to make the sum telescope.

Rahul Saha - 6 years, 11 months ago
Jack D'Aurizio
Jun 29, 2014

Two key elements are the partial fraction decomposition 1 ( k + 2 ) ( k + 3 ) ( k + 4 ) = 1 / 2 k + 2 1 k + 3 + 1 / 2 k + 4 \frac{1}{(k+2)(k+3)(k+4)}=\frac{1/2}{k+2}-\frac{1}{k+3}+\frac{1/2}{k+4} and the identity: k = 0 n ( 1 ) k k + η + 1 ( n k ) = 0 1 x η k = 0 n ( n k ) ( x ) k d x = 0 1 x η ( 1 x ) n = η ! ( n + η + 1 ) ( n + 1 ) . \sum_{k=0}^n\frac{(-1)^k}{k+\eta+1}\binom{n}{k}=\int_{0}^{1}x^\eta\sum_{k=0}^{n}\binom{n}{k}(-x)^k\,dx=\int_{0}^{1}x^\eta (1-x)^n = \frac{\eta!}{(n+\eta+1)\cdot\ldots\cdot(n+1)}. This two (pretty advanced) ingredients give that the original sum is just 1 2 ( n + 3 ) ( n + 4 ) . \frac{1}{2(n+3)(n+4)}.

Is there any way to make the sum telescope somehow?Not having any idea about integration,I would like to see a calculus-free solution.

Rahul Saha - 6 years, 11 months ago
Souryajit Roy
Jul 10, 2014

k = 0 n ( 1 ) k k 3 + 9 k 2 + 26 k + 24 ( k n ) \sum_{k=0}^{n}\frac{(-1)^{k}}{k^{3}+9k^{2}+26k+24}(_{k}^{n})

= k = 0 n ( 1 ) k ( k + 2 ) ( k + 3 ) ( k + 4 ) ( k n ) =\sum_{k=0}^{n}\frac{(-1)^{k}}{(k+2)(k+3)(k+4)}(_{k}^{n})

= k = 0 n ( 1 ) k k + 1 ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + 4 ) ( k + 4 n + 4 ) =\sum_{k=0}^{n}(-1)^{k}\frac{k+1}{(n+1)(n+2)(n+3)(n+4)}(_{k+4}^{n+4})

= 1 ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + 4 ) k = 4 n ( 1 ) k ( k 3 ) ( k n + 4 ) =\frac{1}{(n+1)(n+2)(n+3)(n+4)}\sum_{k=4}^{n}(-1)^{k}(k-3)(_{k}^{n+4})

k = 0 n + 4 ( 1 ) k ( k 3 ) ( k n + 4 ) \sum_{k=0}^{n+4}(-1)^{k}(k-3)(_{k}^{n+4})

= k = 0 n + 4 ( 1 ) k k ( k n + 4 ) 3 k = 0 n + 4 ( 1 ) k ( k n + 4 ) =\sum_{k=0}^{n+4}(-1)^{k}k(_{k}^{n+4})-3\sum_{k=0}^{n+4}(-1)^{k}(_{k}^{n+4})

= k = 1 n + 4 ( 1 ) k k ( k n + 4 ) 3 ( 1 1 ) n + 4 =\sum_{k=1}^{n+4}(-1)^{k}k(_{k}^{n+4})-3(1-1)^{n+4}

= 1 n + 4 k = 1 n + 4 ( 1 ) k ( k 1 n + 3 ) =\frac{1}{n+4}\sum_{k=1}^{n+4}(-1)^{k}(_{k-1}^{n+3})

= 1 n + 4 ( 1 1 ) n + 3 = 0 =\frac{1}{n+4}(1-1)^{n+3}=0

Hence, k = 4 n ( 1 ) k ( k 3 ) ( k n + 4 ) \sum_{k=4}^{n}(-1)^{k}(k-3)(_{k}^{n+4})

= k = 0 3 ( 1 ) k ( k 3 ) ( k n + 4 ) =-\sum_{k=0}^{3}(-1)^{k}(k-3)(_{k}^{n+4})

= 3 ( 0 n + 4 ) 2 ( 1 n + 4 ) + ( 2 n + 4 ) = ( n + 1 ) ( n + 2 ) 2 =3(_{0}^{n+4})-2(_{1}^{n+4})+(_{2}^{n+4})=\frac{(n+1)(n+2)}{2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...